Intelligent Hazard Assessment of Mangrove Degradation - Ryabtsev, Vladimir; Rahmadi, M Taufik; Harefa, Meilinda Suriani; Tuhono, Eling; Suciani, Ayu; Pratama, Alvin (MO.RI Publishing, 2024)
Mangrove ecosystems are crucial for mitigating climate change by sequestering significant amounts of carbon, providing habitat for diverse species, and protecting coastal areas. Their sustainability is vital for global environmental balance and human welfare. Analysis using the Eidos system reveals the threats to mangrove forest health, considering both negative and positive factors and analyzing the strength and direction of each threat's influence. The Eidos system facilitated the development of a statistical model and cognitive system, demonstrating effectiveness in identifying and classifying degradation risks based on empirical data, allowing for early predictions at relatively low operational costs. These findings can be leveraged by coastal protection organizations worldwide, as the Eidos system is freely accessible online in multiple languages. The results have the potential to inform targeted mangrove conservation policies and enhance environmental protection initiatives in various regions.